Impact of Soil Tillage Methods on Bulk Density - Alijon, Jurayev; Mohira, Olimova; Ilgorbek, Muqimjonov (American Journal of Biology and Natural Sciences, 2024)
Soil tillage methods significantly influence the physical and mechanical properties of soil, including bulk density, which is a critical parameter in soil health and crop productivity. This study evaluates the effects of different tillage practices on the bulk density of loamy soils under experimental conditions. Methods such as deep tillage, shallow tillage, and no-tillage were analyzed to determine their impacts on soil structure, water infiltration, and aeration. Results indicate that deep tillage effectively reduces bulk density and enhances soil structure, while minimal or no-tillage retains natural soil conditions with limited improvement in physical properties. These findings provide actionable recommendations for optimizing tillage practices to improve agricultural outcomes.